If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5x + 2y = -17 Solving 5x + 2y = -17 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2y' to each side of the equation. 5x + 2y + -2y = -17 + -2y Combine like terms: 2y + -2y = 0 5x + 0 = -17 + -2y 5x = -17 + -2y Divide each side by '5'. x = -3.4 + -0.4y Simplifying x = -3.4 + -0.4y
| -6x-2y=24 | | 2x(a+c)= | | 3x^4-15x^3+6x^2-30x=0 | | 3x^4-15x^3+6x^2-30=0 | | 10d-15=12d | | x^4+2x^3+3x^2+18x-54=0 | | 3(x-7)+4(x+4)= | | -6y=24 | | -2(3-x)=30 | | .50y=1.5 | | 15a-2(4a+5)=-6a | | 3*12=.4y | | 10=5y-3y | | 6x-3x=12 | | -6(4-2x)=12x-24 | | 4x-3x=5 | | 2.5x+1.0x=7 | | 6x+33=5x | | 5m+3=18 | | -2n+3x=7 | | .50b+6=11 | | 8-x=12-2x | | b=9b-24 | | 9y^2-33y+24= | | -9+2(4g-7)=9 | | x+4=9-2x | | m+4+5=22 | | 33=x+4 | | z=1+i^12 | | 14+4=x+5x | | -160+-52x+1x^2+x^3=0 | | 5x(3x+5)=0 |